Sistem Pengkodean Data Pada File Teks Untuk Keamanan Informasi Dengan Menggunakan Metode Skipjack - Suprianto Suprianto; Asep Ririh Riswaya (Jurnal Computech & Bisnis (e-Journal), 2018)
Nowadays internet has become the important part in the IT. With so many the internet users from the large company to the personal users make a lot of the developing data. With the development of data so many people appeared who wants to know the others data for their own advantage, the are called hacker.This could be avoid with the encryption of data which will be sent so can’t be read by the unimportant people, there’s a few way to encryption data, The writer choose the encryption data with skipjack method. This method is how to encrypt text file which came from an internet application, such as e-mail service which has 32 stage include the permutation pattern and rule A, rule B which are part of this method.With the method the data which will be sent through the internet is encrypt by the sender. Then after it is received, the encrypted data or the chipertext will be decrypted into the previous data or plaintext.The use of skipjack method with the software has been made, the process of encryption and decryption are proved can help to keep the information valid which is come from the sender to the receiver. Keyword : Hacker, Skipjack Method, "Skipjack Security Software", valid information.